2018
DOI: 10.1002/ecs2.2148
|View full text |Cite
|
Sign up to set email alerts
|

Geology drives the spatial patterning and structure of termite mounds in an African savanna

Abstract: Citation: Muvengwi, J, AB Davies, F Parrini, and ETF Witkowski. 2018. Geology drives the spatial patterning and structure of termite mounds in an African savanna. Ecosphere 9(3):e02148. 10.1002/ecs2.2148Abstract. Termite mounds perform important roles in savanna ecosystems, generating heterogeneity and influencing ecosystem processes across multiple trophic levels. However, the influence the environment and neighboring termite colonies have on mound spatial patterning and structure is poorly understood, despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…(1999) and Muvengwi et al. (2018) in Gonarezhou National Park where densities of 0.73/ha and 6.1/ha, respectively, were recorded on granite landscape zones. However, the Macrotermes mound densities from this study are similar to those reported from the natural vegetation by Debelo and Degaga (2014) in the Central Rift Valley of Ethiopia (9.6/moundsha) and Boga et al.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…(1999) and Muvengwi et al. (2018) in Gonarezhou National Park where densities of 0.73/ha and 6.1/ha, respectively, were recorded on granite landscape zones. However, the Macrotermes mound densities from this study are similar to those reported from the natural vegetation by Debelo and Degaga (2014) in the Central Rift Valley of Ethiopia (9.6/moundsha) and Boga et al.…”
Section: Discussionmentioning
confidence: 91%
“…The distribution and density of termite mounds in an area is influenced by the landscape, termite species, mound activity status, size and ages of colonies (Davies et al, 2014;Grohmann, Oldeland, Stoyan, & Linsenmair, 2010;Korb & Linsenmair, 2001a;Levick et al, 2010;Meyer, Braack, Biggs, & Ebersohn, 1999;Muvengwi, Davies, Parrini, & Witkowski, 2018). Meyer et al (1999) in a study on the mound distribution in a pristine natural area in the Vhembe District, northern Kruger National Park, found that soil type, geography and termite species influenced mound densities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future work could include consideration of other environmental control variables or metrics such as the Compound Topographic Index (Marthews et al 2015) or a combination of variables that can be used to indicate moisture availability or other soil characteristics. Geologic heterogeneity influences vegetation (Cleverly et al 2016, Githumbi et al 2018, Muvengwi et al 2018), so being able to statistically show the impact of geology and geology on variables such as soil moisture at fine resolution could improve inference on phenoregion assignment. This study could also be expanded by continuing the analysis on other national parks in East Africa along the megatransect.…”
Section: Discussionmentioning
confidence: 99%
“…In Fig. 1 , we show a small sample from such diversity, including fairy circles in semiarid environments ( 1 ), regular and random tiling of termite mounds ( 2 , 3 ), and more randomly spaced ant nests and trees ( 4 , 5 ). This variation is not limited to between taxa but also varies between different plots in the same region.…”
mentioning
confidence: 99%